ANALYZING THE IMPACT OF GRIEVING ON MILES’ CHARACTER IN THE NOVEL UGLY LOVE - Paputungan, Seysha Apriella; Baga, Magdalena; Podungge, Rusni (Universitas Gunadarma, 2025)
The painful loss can influence one character's development as described by psychological fiction work. Coleen Hoover's book Ugly Love follows the protagonist's emotional journey following the deaths of his mother and kid. The purpose of this study is to investigate the psychological effects of grieving on the main character, Miles Archer using Kübler-Ross's theory of the grief five stages. Using qualitative method and a literary psychology approach, this study traces the main character's journey to acceptance while examining how his self-destructive actions and relationship patterns reflect unresolved grief. The findings of this study are showing that the main character attempts to confront his trauma, seek reconciliation, and begin emotional healing. This study highlights how stories related to grief in literature can reflect people’s emotional experiences in real life, which reveals the deep grief. According to the study's findings, addressing the psychological effects of loss in fictional characters shows the effects of personal development and wholesome relationships.